2019
DOI: 10.1590/s1984-296120180067
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological findings of Fasciola hepatica infection in non-native European hare (Lepus europaeus) in Southern Chile

Abstract: Fasciola hepatica is a parasite introduced in America from Europe, being considered of concern for public health and animal production, especially in countries with endemic areas as occur in Chile. In this country, the research has been focused mainly in domestic ruminants, with native and introduced wildlife being largely ignored. Thus, the aim of this study was to report the infection by Fasciola hepatica in an introduced mammal, the European hare, which is distributed along a vast area of the country. One i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…65 A description of histopathologic changes caused by F. hepatica natural infection in the European hare (Lepus europaeus) reported hyperplasia of bile ducts with inflammatory cells and chronic fibroblastic response and portal fibrosis. 66 Similar findings were described in a different study including Sika deer from Hokkaido Japan. In this study, a higher burden of infection (45% prevalence) was documented in deer slaughtered for human consumption.…”
Section: Liver Parenchyma Pathologysupporting
confidence: 83%
“…65 A description of histopathologic changes caused by F. hepatica natural infection in the European hare (Lepus europaeus) reported hyperplasia of bile ducts with inflammatory cells and chronic fibroblastic response and portal fibrosis. 66 Similar findings were described in a different study including Sika deer from Hokkaido Japan. In this study, a higher burden of infection (45% prevalence) was documented in deer slaughtered for human consumption.…”
Section: Liver Parenchyma Pathologysupporting
confidence: 83%
“…Supporting the current study, Hussain & Zghair (2017) and Trivilin et al (2014) reported haemorrhage points on the parietal surface in chronically infected livers, representing the points of entrance of the immature parasites into the liver structure, and enlarged/distended ducts, caused by immunological reaction of macrophages and lymphocytes infiltration during the later stage of fasciolosis. Oyarzún-Ruiz et al (2019) reported that biliary ducts hyperplasia and hypertrophy with fibroblastic formation, as also observed in infected wild rabbits in Chile. Some of the external lesions were observed in the livers from Experiment 2.…”
Section: Discussionmentioning
confidence: 61%
“…Oyarzún-Ruiz et al . (2019) reported that biliary ducts hyperplasia and hypertrophy with fibroblastic formation, as also observed in infected wild rabbits in Chile. Some of the external lesions were observed in the livers from Experiment 2.…”
Section: Discussionmentioning
confidence: 66%
“…They determined in the same study that thrombosis occurred in the blood veins of the parasite migration routes. The study by Oyarzún-Ruiz et al (2014) identified hyperplasia and hypertrophy in the bile ducts and inflammation in some bile ducts. In the same study, they detected fibrosis and granulomatous response in the liver parenchyma.. Al-Khafaji et al ( 2020) detected hemorrhage cholangitis, and pericholangitis associated with fibrosis caused by adult parasite migration in the liver parenchyma.…”
Section: Discussionmentioning
confidence: 99%